KONSEP KOSMOLOGI MENURUT JALALUDDIN RUMI DAN IMPLIKASINYA TERHADAP CARA MEMPERLAKUKAN ALAM SEMESTA - Herdeni Herdeni; Idrus al-Kaf; M. Arpah Nurhayat (JURNAL AL-AQIDAH, 2022)
The talk of cosmology is a very interesting matter. Because studied by scientists, theologians and also Sufis. Cosmology according to Annaemarie Schimmel is categorized as Islamic mysticism. Jalaluddin Rumi is a Sufi figure who studies cosmology. Jalaluddin Rumi is able to explain or interpret the secrets of God and His creation by using poetry (in the form of imagery) with high love. The purpose of this research is to study or analyze Jalaluddin Rumi's concept of cosmology and its implications for how to treat the universe. This research is a research library (library research), using the description method. Then the analysis uses the historical continuity method. And continued with the internal communication method, with this method the works of Jalaluddin Rumi were analyzed. The result of this research is cosmology according to Jalaluddin Rumi that Allah SWT created this universe as a mirror of Himself, because all of this creation is none other than His tajalli. Allah, who was previously a hidden treasure, then manifests, appears and appears in His creation. Then Rumi also said that the motive for the creation of nature by God is love. It is love that prompted God to create nature. The implication of how to treat the universe is that humans must protect nature such as taking care of themselves, communicating well with nature, and not destroying the existing order of life.